GAMBARAN KEPERCAYAAN DIRI SISWA KELAS VIII DI SMPN 2 CIMAHI - Nabila Meiliana Salsabila (IKIP Siliwangi, 2022)
The purpose of this research is to see how the level of self-confidence of students in SMP Negeri 2 Cimahi. The research conducted here uses qualitative methods. The data collection used is through observation, interviews, and documentation. The research subjects here are 7 students who have low self-confidence in SMP Negeri 2 Cimahi. Self-confidence can affect individual success both in learning, work environment, family environment, and in social relationships with others. Individuals who have good self-confidence, they have confidence and always try to develop their potential to the fullest and show the best of themselves and are proven by an achievement. Therefore self-confidence can affect the development process of students, but it is often found that students who have low self-confidence in the school environment, they tend not to like the changes that exist in themselves, rarely get along with their classmates, are often alone in class, do not have confidence in themselves. the ability possessed so that when in class the teacher asks questions students prefer to be silent even though they know the answer because of a lack of confidence. The results obtained stated that the VIII grade students at SMPN 2 Cimahi had low self-confidence and the contributing factors were the family economy and the environment of their peers. Keywords: Self-confidence, causal factors